Point-of-care tests in the emergency medical services: a scoping review - T. H. M. Moore; S. Dawson; K. Kirby; R. Body; A. Thompson; Y. O. Adepoju; R. Perry; H. Nicholson; J. Dinnes; K. Mitchell; J. Savović; S. Voss; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background This scoping review aimed to summarize existing research on point-of-care tests (POCTs) within emergency medical services (EMS). There is a lack of comprehensive reviews covering the breadth and scope of application of POCTs in EMS despite growing interest and potential benefits in this setting. A review of the research will inform how we target future research efforts to support effective implementation and avoid duplication. Methods We searched three databases to April 2023 using comprehensive terms for POCTs. One author screened titles and abstracts, full-text papers and extracted data with a second author checking the data. A scoping review framework was used to categorise studies according to demographics, study design, medical conditions, biomarkers and test devices. Results We found 141 papers that included 158 reports of 9 study designs, 155 reports of 40 combinations of biomarker and condition and 161 reports of 41 test-devices. The majority of research was done in the UK (19%), US (17%), and the Netherlands (16%), mostly in land-based EMS (82%). Most frequently assessed were troponin for acute coronary syndromes (26%), lactate for sepsis (14%) or lactate for trauma/critical illness (13%). The majority of research designs investigated the accuracy of the tests (43%). Few studies were of a design to inform guidelines to change patient pathways and the associated outcomes, including, randomised controlled trials (RCTs) (4%), non-randomised studies able to assess causality (6%), economic analyses (1%) or qualitative work on acceptability (3%). In those few cases where RCTs were done there were long delays between initial test-accuracy research and publication of the first RCT, for example 11 years delay for troponin for acute coronary syndromes. Conclusions We identified a thriving base of research on POCT in the EMS, however most studies established the diagnostic accuracy of the tests with few RCTs, economic analyses or qualitative research on acceptability. The time-lag from diagnostic accuracy to developing an RCT is considerable. Investment in funding and infrastructure is needed to support the research pathway for potential POCTs beyond diagnostic accuracy to designs able to assess clinical effectiveness, acceptability and economic effectiveness.